Bronchogenic carcinoma in sample of Iraqi patients, Fiber optic bronchoscope findings - Al,Jobouri, Adnan M.; Sultan, Kassim M.; Al.Obaidy, Muhammed W.; Shihab, Firas R. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Lung cancer is the leading cause of cancer deaths and its incidence is rising. The determination of histopathology and stage of primary lung carcinoma is crucial to develop appropriate treatment approach that affects morbidity and mortality. Fiber optic bronchoscope techniques for early detection of lung cancer are a promising tool as they might allow visualizing changes of early lung cancer and also permitting sampling for histological confirmation.Objective: This study was intended to compare the fiber optic bronchoscopy findings and their anatomical locations with the histopathology types in patients with lung cancer.Patient and Methods: A cross section study was conducted during the period from 1st February 2012 to the 31th of July 2013, 49 patients with clinical and radiological findings suggesting primary lung cancer and diagnose later by bronchoscope samples as cases of primary lung cancer chosen for analysis of their bronchoscope findings, at Baghdad teaching hospital / respiratory clinic.Results: Patients with squamous carcinoma (31%) had (67%) visible mass and (13%) presented invisibly as external compression. Patients with adenocarcinoma (41%) had (40%) visible mass and (35%) presented invisibly as external compression while normal bronchoscope was seen in (30%) of those patients so that adenocarcinoma mostly invisible. Patients with small cell carcinoma (28%) had (50%) visible mass and (21%) presented invisibly as external compression.The location of finding in (27%) of the patients with squam. ous carcinoma was in the right main bronchus and (20%) in right upper lobe bronchus while the carina affected in (47%). Patients with adenocarcinoma have vocal cord affected in (25%) and left upper lobebronchus lesion in (25%).Conclusion: There was no relationship between the fiber optic bronchoscope findings and their anatomical locations with the histological types of lung.